A qualitative analysis of staff-client interactions within a breast cancer assessment clinic. Issue 1 (February 2017) - Nightingale, J.M.; Murphy, F.; Eaton, C.; Borgen, R.
Abstract: Objectives: Breast screening clients recalled to an assessment clinic experience high levels of anxiety. The culture of the assessment clinic may impact upon client experience, which may influence their future re-engagement in screening. This study aimed to explore the culture of staff-client interactions within a breast cancer assessment clinic. Materials and methods: Following an ethnographic approach, twenty-three client journeys were observed, followed by semi-structured interviews with the clients. The observation and interview data were analysed to produce research themes, which were then explored within two focus groups to add a practitioner perspective. Results: Multiple staff-client interaction events were observed over a period of several weeks. Client interview feedback was overwhelmingly positive. Three recurrent and sequential themes emerged: breaking down barriers, preparing the ground and sign-posting . These themes outline the changing focus of staff-client interactions during the client's clinic journey, encompassing how anxieties were expressed by clients, and responded to by practitioners. Conclusion: This study was the first to explore in depth the staff-client interaction culture within a breast assessment clinic using an ethnographic approach. A new perspective on professional values and behaviours has been demonstrated via a model of staff-client interaction. The model documents the process of guiding the client from initial confusion and distress to an enhanced clarity of understanding. A recommendation most likely to have a positive impact on the client experience is the introduction of a client navigator role to guide the clients through what is often a lengthy, stressful and confusing process. Highlights: This study was the first to explore staff-client interaction within breast assessment clinics. Assessment clinic culture may affect client perceptions and future re-engagement in screening. An ethnographic approach outlined how client anxiety was exhibited and responded to by staff. A 'client navigator' role is recommended to guide the client through a stressful journey. Study recommendations may serve as 'best practice' checklists for other assessment units.